1978
DOI: 10.1161/01.cir.57.4.692
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between apexcardiographic and angiographic indexes of left ventricular performance in patients with aortic incompetence.

Abstract: Left ventricular (LV) apexcardiogram (ACG) and its first derivative (dA/dt) was obtained in 104 normal subjects and 34 patients with chronic aortic incompetence (AI). In the patients with AI the ACG was recorded simultaneously with LV pressure (tipmanometer). The systolic upstroke time (SUT), the time to peak dA/dt (t-dA/dt) and the a wave percentage amplitude (a/H) of the ACG was measured. In normal subjects SUT averaged 99 +/- 17 (SD) msec. In 17 patients with AI and normal ejection fraction (EF) (group 1) S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1979
1979
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“… 35 , 36 Prior studies using a pulse-tracing technology in the apex cardiogram reported that prolonged UT was associated with an increase in left ventricular wall stress and a decrease in left ventricle function. 37 , 38 This age-induced decline in cardiac function probably led to the prolonged UTc in this study.…”
Section: Discussionmentioning
confidence: 66%
“… 35 , 36 Prior studies using a pulse-tracing technology in the apex cardiogram reported that prolonged UT was associated with an increase in left ventricular wall stress and a decrease in left ventricle function. 37 , 38 This age-induced decline in cardiac function probably led to the prolonged UTc in this study.…”
Section: Discussionmentioning
confidence: 66%
“…It has been demonstrated that left apexcardiogram reflects quantitatively pressure changes within the left heart in a temporal fashion [17], Furthermore, we have shown that time and relative height diastolic indices of apex tracing correlated closely with corresponding intra cardiac measurements of relaxation and compliance using simultaneous high-fidelity tracings during heart catheter ization [18][19][20][21]. In the present study, 30 years after its introduction [22,23], the usefulness of exercise apexcardiography has been reevaluated using new criteria for exactly defining the changes of diastolic indices during low-level isometric stress.…”
mentioning
confidence: 63%
“…On the other hand, it has been noted that the configu ration, time course and slope of the left apexcardiogram are significantly correlated with left ventricular pressure [18,19,[34][35][36][37][38][39]. We have first described the temporal coincidence of the onsets of systolic upstrokes and, in part, also of the diastolic nadirs of apex and left ventricu lar pressure tracings using simultaneous high-fidelity trac ings during diagnostic heart catheterization [17,18].…”
Section: Monolas Types Of Diastolic Dysfunction During Handgripmentioning
confidence: 99%
“…In addition, UT could be a parameter of left ventricular function and geometry [30,44,45]. Abnormal cardiac function, including left ventricular hypertrophy, reduced left ventricular ejection fraction, and increased left ventricular filling pressure and wall stress, have been associated with poor cardiovascular outcomes in patients with CKD [46][47][48].…”
Section: Discussionmentioning
confidence: 99%